An Unusual Taphonomic Case Report of Human Skeletal Remains in an Urban Aqueduct - Ellen E.I. Fricano; Stephanie A. Torres; Alicia Morgan (American Journal of Forensic Medicine & Pathology, 2026)
Decomposition patterns and taphonomic changes associated with aquatic environments present unique challenges for forensic interpretation because they are influenced by the complex interactions among water temperature, flow dynamics, sediment deposition, and animal scavenging. The authors present an unusual case of water-submerged human remains that were discovered in a large, municipal, clean water feeder pipe. The remains were exposed to high-pressure, continuous water flow for several years, resulting in multiple distinctive postmortem alterations that should be considered in future cases. The remains exhibited plastic deformation and creep rupture, including ribs permanently deformed at an acute angle and highly localized abrasion that wore away large areas of certain elements. This unusual case highlights the need for knowledge of the scene, a greater understanding of decomposition and taphonomic processes in treated aquatic sites, and the importance of intrinsic bone biomechanical characteristics that affect fracture patterns.